Loss of p53 compensates osteopenia in murine Mysm1 deficiency - Haffner-Luntzer, Melanie; Brinker, Titus Josef (The FASEB journal, 2018)
Histone modifications critically contribute to the epigenetic orchestration of bone homeostasis—in part, by modifying the access of transcription factors to specific genes involved in the osteogenic differentiation process of bone marrow mesenchymal stem cells (MSCs) and osteoblasts. Based on our previous finding that histone H2A deubiquitinase 2A-DUB/Mysm1 interacts with the p53 axis in hematopoiesis and tissue development, we analyzed the molecular basis of the skeletal phenotype of Mysm1-deficient mice and dissected the underlying p53-dependent and -independent mechanisms. Visible morphologic, skeletal deformations of young Mysm1-deficient mice—including a kinked and truncated tail and shortened long bones—were associated with osteopenia of long bones. On the cellular level, Mysm1-deficient primary osteoblasts displayed reduced potential to differentiate into mature osteoblasts, as indicated by decreased expression of osteogenic markers. Reduced osteogenic differentiation capacity of Mysm1-deficient osteoblasts was accompanied by an impaired induction of osteogenic transcription factor Runx2. Osteogenic differentiation of Mysm1−/− MSCs, however, was not compromised in vitro. In line with defective hematopoietic development of Mysm1-deficient mice, Mysm1−/− osteoclasts had reduced resorption activity and were more prone to apoptosis in TUNEL assays. Skeletal alterations and osteopenia of Mysm1-deficient mice were phenotypically completely rescued by simultaneous ablation of p53 in p53−/−Mysm1−/− double-deficient mice—although p53 deficiency did not restore Runx2 expression in Mysm1−/− osteoblasts on the molecular level but, instead, enhanced proliferation and osteogenic differentiation of MSCs. In summary, our results demonstrate novel roles for Mysm1 in osteoblast differentiation and osteoclast formation, resulting in osteopenia in Mysm1-deficient mice that could be abrogated by the loss of p53 from increased osteogenic differentiation of Mysm1−/−p53−/− MSCs.—Haffner-Luntzer, M., Kovtun, A., Fischer, V., Prystaz, K., Hainzl, A., Kroeger, C. M., Krikki, I., Brinker, T. J., Ignatius, A., Gatzka, M. Loss of p53 compensates osteopenia in murine Mysm1 deficiency.
Gesehen am 20.08.2019